Determination of Antioxidants and Antimicrobial Activities of Platytaenia multicaule - Kakar, Najeebullah; Samiullah; Khan, Naqeebullah; Kakar, Attiq-ur-Rehman; Bakhsh Tareen, Rasool; Meer, Nazia; Waheed Ahmed Shah, Syed; Ali, Irshad; Asghar, Muhammad; Baqi Achakzai, Abdul (Al-Nahrain Journal of Science, 2019)
Determination of antioxidants and antibacterial activities of an important medicinal plant like Platytaenia multicaule has been accomplished for the first time in this contest. Regarding antioxidants and antibacterial activities, the plant was analyzed chemically by means of four well known methods as well as by UV/VIS spectroscopic techniques. The crude extract was obtained from the plant by the utilization of methanol (MeOH) and the antioxidants activities of the crude extract tested. Furthermore, using spectrophotometer the antioxidants capacities were examined via 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) Assay, Total Antioxidant Capacity (TAC), Ferric Reducing Antioxidant Power (FRAP) Assay and Reducing Power (RP) Assays. The capacity of DPPH Assay of P. multicaule was 190 mg/g of ascorbic acid concentration. Additionally, for the TAC and FRAP the values of extracts were 10.85 mg and 40 mg of ascorbic acid/g of P. multicaule extract respectively. In addition, the RP shows 3.29 mg/g of ascorbic acid concentration. The P. multicaule have shown the high antioxidant activity. On the other hand, the antibacterial activity of this plant was investigated by the agar well diffusion method. In this, the plant extracts were examined against two bacteria namely Escherichia coli and Staphylococcus aureus which exhibited 14 mm and 16 mm zones of inhibition respectively. Hence, this test proved that the P. multicaule contains high antibacterial agents.